1975
DOI: 10.1111/j.1365-2222.1975.tb01840.x
|View full text |Cite
|
Sign up to set email alerts
|

Appearance of basophils in the sputum of patients with bronchial asthma

Abstract: Summary A total of 108 samples of sputum obtained from twenty patients with bronchial asthma were examined for appearance of basophils and eosinophils. Both cell types are present in sputum during an asthmatic attack and disappear at the conclusion of the attack. Their presence correlates with the severity of the disease. It has previously been demonstrated that the blood basophils count falls during attacks of bronchial asthma, and the present study suggests that basophils move from the blood stream into bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

1977
1977
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(23 citation statements)
references
References 4 publications
0
23
0
Order By: Relevance
“…Basophils have been found in nasal se cretions by some investigators [6] but not by others [11], If cells were the only source of the histamine found in nasal secretions, they must have been present in larger num bers in nasal secretions than in blood, and their numbers must fluctuate rapidly in nor mals and allergies. Neither possibility seems likely, although the findings of Kimura et al [16] that basophils may be found in asth matic sputum collected during acute symp toms but not during symptomatic periods would suggest that basophilic chemotactic factors exist and could cause fluctuations in basophil content in sputum. Further studies comparing cytology and histamine determi nations are needed to determine what pro portion of histamine in nasal secretions is extracellular.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Basophils have been found in nasal se cretions by some investigators [6] but not by others [11], If cells were the only source of the histamine found in nasal secretions, they must have been present in larger num bers in nasal secretions than in blood, and their numbers must fluctuate rapidly in nor mals and allergies. Neither possibility seems likely, although the findings of Kimura et al [16] that basophils may be found in asth matic sputum collected during acute symp toms but not during symptomatic periods would suggest that basophilic chemotactic factors exist and could cause fluctuations in basophil content in sputum. Further studies comparing cytology and histamine determi nations are needed to determine what pro portion of histamine in nasal secretions is extracellular.…”
Section: Discussionmentioning
confidence: 68%
“…Bronchial secretions have been shown to contain appreciable numbers of cells in primates [21] and humans [16,22]. Basophils have been found in nasal se cretions by some investigators [6] but not by others [11], If cells were the only source of the histamine found in nasal secretions, they must have been present in larger num bers in nasal secretions than in blood, and their numbers must fluctuate rapidly in nor mals and allergies.…”
Section: Discussionmentioning
confidence: 99%
“…Histamine-containing cells have been demon strated in bronchial secretions [9][10][11], and histamine release from these cells can be induced by a variety of stimuli. IgE-mediated release of histamine into nasal secretions [12] might be expected to occur in patients with allergic rhinitis.…”
mentioning
confidence: 99%
“…It is not clear at present whether basophils play a causative role in asthmatic attacks. However, their participation is suggested by the findings of Kimura et al (10,11) who showed that circulating basophils increase in number during the preattack stage of bronchial asthma and fall during attacks with a concomitant rise in the number of basophils in the sputum of patients.…”
mentioning
confidence: 89%